Zamia brasiliensis, a new species of Zamia (Zamiaceae, Cycadales) from Mato Grosso and Rondônia, Brazil - Segalla, Rosane; Calonje, Michael (Phytotaxa, 2019)
Zamia brasiliensis Calonje & Segalla, a new subterranean-stemmed species of Zamia (Zamiaceae) from Mato Grosso and Rondônia, Brazil, is described and illustrated. It is compared to two morphologically similar species with adjacent geographic distributions: Z. boliviana from the Cerrado biome, and the Amazonian species Z. ulei. The new species shares unarmed petioles with Z. boliviana but is readily distinguishable by its much broader leaflets. Z. brasiliensis has leaflets somewhat resembling those of juvenile individuals of Z. ulei, but the latter species is easily differentiated by the presence of prickles on its petiole.